2017
DOI: 10.3748/wjg.v23.i24.4437
|View full text |Cite
|
Sign up to set email alerts
|

Variability of anti-human transglutaminase testing in celiac disease across Mediterranean countries

Abstract: AIMTo verify the precision and accuracy of transglutaminase antibodies (TGA) assays across Mediterranean countries.METHODSThis study involved 8 referral centres for celiac disease (CD) in 7 Mediterranean countries. A central laboratory prepared 8 kits of 7 blinded and randomized serum samples, with a titrated amount of Human TGA IgA. Each sample was analysed three times on three different days, with each centre running a total of 21 tests. The results were included in a blindly coded report form, which was sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The different test kits cause a problem regarding standardization in the diagnosis [ 15 ]. In their multicenter study including seven Mediterranean countries and 1,974 patients and using eight different kits, Smarrazzo et al [ 16 ] found that a TGA level >1.25 ULN was quite reliable for measurements, and detected the PPV to be 96.1% in cases where the TGA level was >10 ULN. In another Italian study [ 17 ] involving 234 patients, the PPV was determined to be 97.66% in the diagnosis of TGA based on the ESPGHAN criteria (>10 ULN).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different test kits cause a problem regarding standardization in the diagnosis [ 15 ]. In their multicenter study including seven Mediterranean countries and 1,974 patients and using eight different kits, Smarrazzo et al [ 16 ] found that a TGA level >1.25 ULN was quite reliable for measurements, and detected the PPV to be 96.1% in cases where the TGA level was >10 ULN. In another Italian study [ 17 ] involving 234 patients, the PPV was determined to be 97.66% in the diagnosis of TGA based on the ESPGHAN criteria (>10 ULN).…”
Section: Discussionmentioning
confidence: 99%
“…This study has some other limitations in addition to its retrospective nature. In some studies, it is stated that different TGA commercial kits have a high variability rate [ 15 , 16 ]. We did not use different commercial TGA kits in our study, and we consider this to be the most important limitation of our study.…”
Section: Discussionmentioning
confidence: 99%